Early recovery after surgery protocol in orthognathic surgery: a randomized, blind clinical study - Zilane Silva Barbosa de OLIVEIRA; Marcelo Leite Machado da SILVEIRA; Petrus Pereira GOMES; José Sandro Pereira da SILVA; Adriano Rocha GERMANO (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract A randomized, blind and prospective clinical trial was conducted to compare two clinical rehabilitation protocols in patients submitted to orthognathic surgery, during the first 60 days after surgery. Pain, edema, mandibular movement, masticatory efficiency and quality of life were evaluated. Nineteen (19) patients were separated into control and experimental groups. The control group consisted of 10 patients followed by oral and maxillofacial surgeons and submitted to a rehabilitation protocol that involved active and passive mouth opening exercises. The experimental group had 9 patients and followed the surgeons' protocol, in addition to an Early Recovery After Surgery (ERAS) protocol performed by speech therapists, and involving specific motricity exercises and lymphatic drainage. The Student's t-test was applied to compare the results, and the Fisher's exact test of independence, to analyze the quality of life and the masticatory efficiency variables. The statistical significance was set at 5% (p < 0.05) for all the tests. The results showed that the ERAS protocol made a positive difference in pain perception in the first 14 days. However, it did not improve the other variables. Although many variables showed no significant difference, it was concluded that the surgeons can delegate patient rehabilitation to qualified professionals, so that they can optimize their postoperative clinical time.